GATUNKI DOKUMENTACJI PROJEKTOWEJ - Walkiewicz, Barbara (Acta Neophilologica, 2018)
This paper presents genres of design documentation as categorised by literary genetics. Design documentation usually embraces all designs of a given technical object at different stages of its development. Typically, design documentation comprises two designsconceptual (initial) and construction (execution). Building design documentation is a special case of design documentation. Due to its interdisciplinary nature and the complexity of building works and implementation procedures, it includes a series of designs: conceptual design, building permit design, construction (execution) design, tender documentation and “as-built” drawings. All the above mentioned designs are commissioned by the investor, who is a de facto recipient of only one-the conceptual design. The others are aimed at the parties responsible for the approval and execution of a project. The functions of particular designs differ according to the various expectations of their respective recipients, which is reflected in differences at the level of their genre structures.